Long‐Term Trends in Acid Precipitation and Watershed Elemental Export From an Alpine Catchment of the Colorado Rocky Mountains, USA. Issue 11 (21st November 2020) - Crawford, John T.; Hinckley, Eve‐Lyn S.; Neff, Jason C.
Abstract: Acid deposition associated with precipitation is an ecological problem that has affected watersheds in industrialized parts of North America and Europe, but remote landscapes, such as the Colorado Rocky Mountains, have also been impacted. The deposition of strong acids, including nitric and sulfuric acids, has decreased substantially over the past 30 years at Niwot Ridge, a high‐alpine watershed of Colorado. The pH of precipitation has followed these declines and has increased to 5.5. Meanwhile, NH4 +, another important constituent of acid/base balance, and a fertilizing nutrient, has more than doubled in precipitation between 1984 and 2017. A statistical model of long‐term water chemistry concentrations and loads revealed a variety of trends in watershed export of acids and bases, some of which were unexpected, and remain unexplained. For example, despite declining sulfate deposition, sulfate export has increased. On the other hand, watershed nitrate export has remained constant despite decreases in atmospheric deposition, while watershed NH4 + export has increased, albeit minimally, relative to total nitrogen export. Watershed pH and alkalinity appear to have stabilized in response to decreased acid precipitation, which may be explained by geochemical processes, such as carbonate weathering. Overall, in this high‐alpine watershed, atmospheric deposition is trending toward preindustrial conditions, and there is a need to conduct targeted, process‐based studies to determine the mechanisms underlying these trends. The unexpected watershed responses that we identify here require a new framework for understanding acid precipitation recovery. Key Points: Precipitation pH is increasing on Niwot Ridge Surprising stream chemical responses were observed in the Green Lakes Valley The acidity of streams is recovering after decades of elevated acid precipitation